Conserving genetic resources for agriculture: counting the cost - Koo, Bonwoo; Pardey, Philip G.; Wright, Brian D. (International Food Policy Research Institute, 2003)
As improved crop varieties developed by scientific breeding spread throughout the world in the latter half of the 20th century, the risk of excessive reliance by farmers and breeders on a narrowing genetic base was dramatized by the infestation and vulnerability of U.S. hybrid corn with cytoplasm male sterility to southern corn leaf blight. Events like this spurred worldwide efforts to greatly expand the amount of agricultural biodiversity conserved in genebanks. More recently, microarray and other modern biotechnologies that provide new and less costly ways of screening crop samples for useful traits have increased the value of conserved genetic resources and focused worldwide attention on access to and use rights of traditional crop varieties, or landraces, stored in situ (place of origin) or in ex situ genebanks worldwide.